Nitrite and Nitrate in Human Health and Disease - Bryan, Nathan S.; Loscalzo, Joseph; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Humana Press, 2017)
This fully revised and updated new edition provides a comprehensive look at nitrite and nitrate and their effect on human health and disease. The first section describes the biochemical analysis of nitrite and nitrate and its role in human physiology. The book then shifts to sources of human exposure of nitrite and nitrate, including environmental and dietary. Finally, the last section discusses nitric oxide-based therapeutics and how nitrite and nitrate biochemistry can be safely harnessed to improve human health. Each chapter provides a balanced, evidence-based view and heavily cites the most recent published literature. They follow a strict chapter format which includes keywords, key points, a conclusion highlighting major findings, and extensive references. The second edition contains new chapters on nitrite and nitrate in age medicine, nitrite and nitrate as a treatment for hypertension, and nitrite and nitrate in exercise performance. Additionally, the editors have expanded the biochemistry section to include chapters on nitrate reducing oral bacteria, nitrite mediated S-Nitrosation, epigenetics and the regulation of nitric oxide, and nitrite control of mitochondrial function. Nitrate and Nitrite in Human Health and Disease, 2e, will be of interest to health professionals, nutritionists, dieticians, biomedical scientists, and food scientists.
Section I: Biochemistry, Molecular Biology, Metabolism, and Physiology -- Introduction -- From Atmospheric Nitrogen to Bioactive Nitrogen Oxides -- Nitrate Reducing Oral Bacteria: Linking Oral and Systemic Health -- Epigenetics and the Regulation of Nitric Oxide -- The Mitochondrion: A Physiological Target of Nitrite -- Sources of Exposure to Nitrogen Oxides -- Section II: Food and Environmental Exposures to Nitrite and Nitrate -- History of Nitrite and Nitrate in Food -- Nutritional Epidemiology of Nitrogen Oxides: What do the Numbers Mean? -- Nutritional Impact on the Nitric Oxide Pathway -- Dietary Flavonoids as Modulators of NO Bioavailability in Acute and Chronic Cardiovascular Diseases -- Nitrite and Nitrate in Human Breast Milk: Implications for Development -- Regulation of Dietary Nitrate and Nitrite: Balancing Essential Physiological Roles with Potential Health Risks -- Section III: Nitrite and Nitrate in Therapeutics and Disease -- Nitric Oxide Signaling in Health and Disease -- Inhaled Nitric Oxide -- Pharmacology of Nitrovasodilators -- Nitrite and Nitrate in Ischemia-Reperfusion Injury -- The Nitrate-Nitrite-Nitric Oxide Pathway in Traditional Herbal Medicine and Dietary Supplements with Potential Benefits for Cardiovascular Diseases -- Nitrate and Nitrite and Aging and Age-Related Disease -- Nitrite and Nitrate as a Treatment for Hypertension -- Nitrate in Exercise Performance -- Nitrite and Nitrate in Cancer -- Looking Forward.
Keywords: Medicine; Clinical nutrition; Medical biochemistry; Ecotoxicology; Medicine & Public Health; Clinical nutrition; Medical biochemistry; Ecotoxicology